Construction of a pH-responsive, ultralow-dose triptolide nanomedicine for safe rheumatoid arthritis therapy - Liu, Yang; Jin, Jianqiu; Xu, Hao; Wang, Chao; Yang, Yanping; Zhao, Yongjian; Han, Haihui; Hou, Tong; Yang, Guoliang; Zhang, Li; Wang, Yongjun; Zhang, Weian; et al. (Acta biomaterialia, 2021)
Rheumatoid arthritis (RA) is a chronicautoimmune disease, marked by joint swelling and pain, articular synovial hyperplasia, as well as cartilage and bone destruction. Triptolide (TP) is an anti-inflammatory molecule but its use to treat RA is limited due to poor solubility and extremely high toxicity. In this study, by encapsulating TP into a star-shaped amphiphilic block copolymer, POSS-PCL-b-PDMAEMA, we engineered a pH-sensitive TP-loaded nanomedicine (TP@NPs) to simultaneously reduce the toxicity of TP and improve its therapeutic efficacy. TP@NPs shows a uniform spherical structure with a hydrodynamic diameter of ~92 nm and notable pH-responsiveness. In vitro TP@NPs showed reduced cytotoxicity and cell apoptosis of treated RAW264.7 cells compared to free TP. And in vivo intravenous injection of indocyanine green-labeled NPs into a collagen-induced arthritis model in mice showed that the engineered compound had potent pharmacokinetic and pharmacodynamic profiles, while exhibiting significant cartilage-protective and anti-inflammatory effects with a better efficacy and neglible systemic toxicity even at an ultralow dose compared to free TP. These results suggest that TP@NPs may be a safe and effective therapy for RA and other autoimmune diseases. [Display omitted]